Genome-wide identification and evolutionary analysis of NRAMP family genes in tomato (Solanum lycopersicum L.) under cadmium and salt stress - Jun Ma; Shan Li; Necla Pehlivan; Shah Zaman; Ali Anwar (BMC Genomics)
Abstract The Natural Resistance-Associated Macrophage Protein (NRAMP) family consists of integral membrane transporters essential for divalent metal ion transport in plants. This study aimed to identify and characterize NRAMP genes in tomato (Solanum lycopersicum), performing genome-wide classification, and cis-elements analysis, revealing four SlNRAMP genes in the tomato genome. Phylogenetic analysis classified the four SlNRAMP proteins into two distinct groups, group A and group B. The encoded proteins ranged in length from 509 amino acids in SlNRAMP3 to 773 amino acids in SlNRAMP4. The number of predicted transmembrane domains in SlNRAMPs ranged from 12 to 14. Expression analysis in 20 samples from three key developmental stages were collected for metabolic profiling and RNA-seq, revealing that group A genes, including SlNRAMP1 and SlNRAMP2, were predominantly expressed in flowers and mature roots, while group B genes, including SlNRAMP3 and SlNRAMP4, exhibited relatively high expression in leaves and roots, respectively. The SlEIN2 gene, previously misclassified as SlNRAMP5, has now been reassigned to a separate category. Quantitative RT‒PCR analysis demonstrated differential regulation of SlNRAMP expression in roots under cadmium and salt stress. The results highlighted that SlNRAMP4 is critical for cadmium sensitivity, whereas SlNRAMP2 plays a role in the early detection and signaling of NaCl stress. This study provides a detailed characterization of the SlNRAMP family in tomato, advancing our understanding of their roles in metal ion homeostasis and stress responses, while serving as a valuable resource for future research.